Analysis of Students' Learning Difficulty Factors in Circulation System Material in View of Gender Differences - Yenny Putri Sugiyaningrum; Fadhilah Salsabila; Nisrina Zain; Maulidia Mualimah; Mufida Putri Nuri Andini (Journal of Educational Analytics, 2023)
The purpose of this study was to analyze the factors that cause learning difficulties in circulation system material based on gender (male and female). The type of this research was descriptive qualitative research with the research subjects being all students of class XI MIA MA Darul Ma'la, totaling 63 students and the sample was selected using a purposive sampling technique of 10 male students and 10 female students. Research data were collected by means of interviews, questionnaires, and documentation with the research instrument in the form of a Likert scale questionnaire. The results of this study indicate that male students in learning circulation system material have a higher learning difficulty factor than female students, both from internal factors and external factors. Each of these factor percentages, namely, 94.1% and 86%.